2019
DOI: 10.1002/advs.201900180
|View full text |Cite|
|
Sign up to set email alerts
|

Colonic Injuries Induced by Inhalational Exposure to Particulate‐Matter Air Pollution

Abstract: Particulate matter (PM) exposure has been associated with intestinal disorders. Therefore, there is an urgent need to understand the precise molecular mechanism involved and explore potential prevention strategies. In this study, inhaled PM is shown to activate inflammatory pathways in murine colon. In a panel study, it is found that ambient PM levels are significantly associated with elevated number of fecal white blood cells in healthy subjects. Acting as a promoter, PM exposure accelerates chemical carcinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Furthermore, it is essential to study the nano-and microplastics that cross the intestinal barrier; even small quantities of translocated plastic may be as dangerous as or even more dangerous than plastics excreted in the stools. Lastly, in view of the recent literature on the effects of particulate matter in the atmosphere, the impact of airborne microplastics on the intestine should also be assessed [135][136][137].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is essential to study the nano-and microplastics that cross the intestinal barrier; even small quantities of translocated plastic may be as dangerous as or even more dangerous than plastics excreted in the stools. Lastly, in view of the recent literature on the effects of particulate matter in the atmosphere, the impact of airborne microplastics on the intestine should also be assessed [135][136][137].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inhalation, particles and microorganisms released by industrial waste and vehicle exhaust can contaminate food and water supplies, thereby suggesting another route of oral/gastrointestinal exposure ( 109 , 110 ). Recent epidemiological studies have shown a direct link between particulate matter exposure and intestinal defects ( 111 ). Inflammation is a normative response to environmental stressors, even being important for wound healing ( 111 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiological studies have shown a direct link between particulate matter exposure and intestinal defects ( 111 ). Inflammation is a normative response to environmental stressors, even being important for wound healing ( 111 ). Commensal gut bacteria modulate the production of reactive oxygen species and various growth factors responsible for intestinal epithelial migration and proliferation ( 112 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations